Oncological outcomes after piecemeal endoscopic mucosal resection of large non-pedunculated colorectal polyps with covert submucosal invasive cancer. Issue 12 (7th March 2022) - Gibson, Dave J; Sidhu, Mayenaaz; Zanati, Simon; Tate, David J; Mangira, Dileep; Moss, Alan; Singh, Rajvinder; Hourigan, Luke F; Raftopoulos, Spiro; Pham, Alan; Kostos, Phil; Kumarasinghe, M Priyanthi; et al.
Abstract : Objective: Management of covert submucosal invasive cancer (SMIC) discovered after piecemeal endoscopic mucosal resection (pEMR) of large (>20 mm) non-pedunculated colorectal polyps is challenging. The residual cancer risk is largely unknown. We sought to evaluate this in a large tertiary referral cohort. Design: Cases of covert SMIC following pEMR were identified and followed. Oncological outcomes after surgery were divided based on residual intramural cancer, lymph node metastases (LNM) or both. Risk factors for residual intramural cancer and LNM were analysed based on the original pEMR histological variables. Risk parameters were analysed with respect to low and high-risk variables for residual intramural cancer and LNM. Results: Among 3372 cases of large non-pedunculated colorectal polyps, 143 cases of covert SMIC (4.2%) were identified. 109 underwent surgical resection. Histological analysis of pEMR histology was available in 98 of 109 (90%) cases. 62 cases (63%) had no residual malignancy. 36 cases had residual malignancy (residual intramural cancer n=24; LNM n=5; both n=7). All cases of residual intramural cancer could be identified by a R1 histological deep margin. Cases with poor differentiation (PD) and/or lymphovascular invasion (LVI) had a high risk of LNM (12/33), with a very low risk without these criteria (<1%; 0/65). Cases at low risk for LNM with R0 deep margin have a low risk of residual intramural cancer (<1%; 0/35). Conclusion: The majority of cases of large non-pedunculated colorectal polyps with covert SMIC following pEMR will have no residual malignancy. The risk of residual malignancy can be ascertained from three key variables: PD, LVI and R1 deep margin.